Calculus [2nd ed., Vol.1] an Indian adaption - Apostol, Tom M.; Singh, Jitender [con.]; Goyal, Suraj [con.] (Wiley New Delhi, 2023)
Calculus, Second Edition, strikes a perfect balance between theory and technique. Although it differs from the majority of contemporary texts, treating integration before differentiation is the most accurate historical representation of the relationship between the integral and the derivative. This introduces the mean-value theorems and their applications earlier in the text, incorporates a treatment of linear algebra, and contains many new and easier exercises. As in the first edition, an interesting historical introduction precedes each important new concept.
Keywords: Calculus